Exchange rate policy of Austria and Finland: Two examples of a peg - Eduard Hochreiter; Adalbert Knöbl (Bank of Finland, 1991)
In this paper the evolution and experiences of exchange rate strategies in Austria and Finland are analyzed. Following Finland's change of emphasis in the 1980's, both countries now use the exchange rate to achieve low inflation. Experience shows that achieving credibility takes time and is not costless. Austria's policy now seems to be fully credible, but the ultimate test for Finnish exchange rate policy is still to come. The exchange rate peg gives some limited independence for fiscal policy, but it needs to secure a sustainable current account in the medium term. Fixing the exchange rate does not imply the import of unemployment from the center country(ies). Finally, the choice of the peg determines the inflation path but not developments in the real economy.
URN:NBN:fi:bof-201908081365
Keywords: 330